Trauma resuscitation with Low-Titer Group O Whole Blood Or Products: study protocol for a randomized clinical trial (the TROOP trial) - Jan O. Jansen; Claudia Pedroza; Luis Leon Novelo; Tianyao Hao; Gina R. DeWildt; Charles F. Coton; Kiran Mansoor; Shannon W. Stephens; Marisa B. Marques; James R. Stubbs; Jillian R. Richter; Henry E. Wang; et al. (Trials)
Abstract Background Hemorrhage is the most common cause of potentially preventable death after injury. Balanced transfusion with red blood cells, plasma, and platelets (component therapy, CT) has been shown to reduce mortality, and is the standard of care. Low-Titer Group O Whole Blood (LTOWB) is an attractive alternative to CT, but existing evidence comprises observational studies, and a small single center pilot randomized controlled trial, which evaluated a type of whole blood that is no longer in use. The aim of the “Trauma Resuscitation with Low-Titer Group O Whole Blood Or Products” (TROOP) trial is to compare the effectiveness and safety of LTOWB and CT in critically injured patients predicted to require a large volume transfusion. Methods This is a pragmatic, multicenter, Bayesian, sequential non-inferiority/superiority, randomized clinical trial, performed within 15 level I trauma centers in the United States. We aim to randomize 1,100 injured patients to resuscitation with either CT or LTOWB. The primary outcome is 6-h mortality. Secondary outcomes include 24-h and 30-day or hospital mortality (whichever is earlier); prespecified complications; adjudicated cause of death; time to death; length of stay (ICU and hospital); and hospital-, ventilator- and ICU-free days; the incidence of major surgical procedures; time to hemostasis in those undergoing procedures with a hemostatic component; number and type of blood products used until hemostasis is achieved (and randomized products are discontinued), as well as after hemostasis has been achieved, to 24 h post-admission; discharge destination and functional status and quality of life at hospital discharge or 30 days, as measured by Glasgow Coma Scale (GCS) and EuroQol (EQ-5D) quality of life measurement. Discussion This large multicenter clinical trial will contribute high-level evidence on the effectiveness of Low-Titer Group O Whole Blood in the in-hospital management of trauma patients predicted to require a large volume transfusion. Trial registration National Clinical Trial Identified Number: NCT05638581. Clinical trial registry: https://clinicaltrials.gov/study/NCT05638581 First submitted 2022–11-08.